Study on the Spalling Fault Degradation Mechanism and Dynamic Model of Gear Tooth Surfaces - Peng Yi; Wu Shengli; Xing Wenting; Wang Chonghao (Jixie chuandong)
Under the action of alternating load, the initial crack on the gear tooth surface would inevitably initiate and gradually evolve into spalling and other faults. It has a serious impact on the transmission system. More attention is paid to the research when there are apparent faults on the gear tooth surface, and it is difficult to monitor the early faults on the gear tooth surface in real time. Therefore, it is essential to make systematic research on the evolution mechanism of early fault on the gear tooth surface and identify the early fault characteristics of the gear tooth surface in time. According to the improved energy method, a time-varying meshing stiffness model of tooth surface crack initiation and degradation into spalling fault is constructed. Considering the transverse propagation path of the cracks and edge contact effect, the impact of the model on the time-varying meshing stiffness is studied. The results indicate that the impact of surface crack and spalling on the time-varying meshing stiffness is only in a specific area, and the impact of crack length would accelerate the decrease of the meshing stiffness. The spalling width has an impact on the time-varying meshing stiffness, and the spalling length has an impact on the beginning and end of the time-varying meshing stiffness reduction. The spalling edge meshing stiffness would suddenly increase due to the influence of the edge contact.